2017
DOI: 10.1080/21623945.2017.1287637
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of BMP4 in adipogenesis and metabolism

Abstract: BMP4 has a well-established role in triggering commitment of mesenchymal stem cells into the osteogenic and adipogenic linage. We recently described an additional dual function in adipogenesis: after promoting the formation of both white and brown pre-adipocytes, Bmp4 drives terminal differentiation into mature white rather than brown fat cells. Besides this, Bmp4 seems to have a dual role in metabolism either promoting or repressing oxidative metabolism in a cell context dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
(82 reference statements)
4
24
0
Order By: Relevance
“…BMP4 function in bone is complex. 36 Recently, it has been demonstrated that increased circulating levels of BMP4 in obese human subjects and diet-induced obesity (DIO) mice, 37,38 which is often accompanied with osteoporosis, suggesting a osteoporosis promotion role of BMP4. Furthermore, disruption of signalling through BMPR1A in adult osteoblasts or osteoclasts [39][40][41] increases bone mass provides evidence that alteration of the physiologic levels of BMPs and/or altering BMPR1A may have therapeutic effects on bone loss in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…BMP4 function in bone is complex. 36 Recently, it has been demonstrated that increased circulating levels of BMP4 in obese human subjects and diet-induced obesity (DIO) mice, 37,38 which is often accompanied with osteoporosis, suggesting a osteoporosis promotion role of BMP4. Furthermore, disruption of signalling through BMPR1A in adult osteoblasts or osteoclasts [39][40][41] increases bone mass provides evidence that alteration of the physiologic levels of BMPs and/or altering BMPR1A may have therapeutic effects on bone loss in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming Growth Factor-β (TGF-β) family ligands, which include TGF-β, Activin, GDF, and BMP family growth factors, have known roles in both adipogenesis and adipocyte hypertrophy (Lee, 2018, Tang & Lane, 2012, Zamani & Brown, 2011. Thus, TGF-β1, GDF-8, and Activins A and B inhibit adipogenesis (Choy, Skillington et al, 2000, Hirai, Yamanaka et al, 2005, Hoggard, Cruickshank et al, 2009, Ignotz & Massague, 1985, Kim, Liang et al, 2001, Lee, Pickering et al, 2019, Luo, Guo et al, 2019, Sparks, Allen et al, 1992, whereas several BMPs have been shown to promote adipogenesis and/or adipocyte hypertrophy (Gustafson, Hammarstedt et al, 2015, Huang, Song et al, 2009, Modica & Wolfrum, 2017, Schreiber, Dorpholz et al, 2017, Tang, Otto et al, 2004, Tseng, Kokkotou et al, 2008. Yet in spite of a large body of work in this area, fundamental questions remain unresolved, including what steps of adipogenesis are regulated by specific TGF-β family pathways, how are intracellular signaling pathways activated to direct adipocyte development, and can extracellular TGF-β family inhibitors help control adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, BMP4 treatment suppressed UCP-1 expression while increasing lipid accumulation in brown preadipocytes [ 223 ]. However, the role of BMP4 on the differentiation of brown and beige adipocytes is controversial [ 252 ]…”
Section: Enzyme-linked Receptorsmentioning
confidence: 99%